Evaluation of Documentation Management and Business Continuity in Financial Institutions: A Case Study of Unique Sacco In Kabale Municipality. - Komugisha, Susan (Kabale University, 2023)
The study evaluated documentation management and business continuity in financial institutions a case study of Unique SACCO in Kabale Municipality. The objectives of the study were; to identify the types of documents kept at Unique SACCO, to establish the relationship between documentation management and business continuity at Unique SACCO and to examine the documentation management practices used at Unique SACCO. A descriptive research design was used and data was collected using interviews and questionnaire. Quantitative data was analyzed using Microsoft excel to general rabies and qualitative data was analyzed using content analysis method. The study revealed that documents kept at Unique SACCO were; statement of cash flows, employment documents, bills and receipts, inventories of goods, financial documents, financial statements and balance sheet. The study on the relationship between documentation management and business continuity were; enables the SACCOs to operate effectively, assists in the planning of the organization, help to improve in service delivery, improves on the efficiency and productivity of the SACCO, essential informational resource, inventory is effectively managed and ensures easily information accessibility. The study recommended there should be employment of skilled workers to enable provision of effective and efficient services in document management at Unique SACCO for easy access and retrieval of the documents, the SACCO should provide enough capital to help the records department to perform its duties in document management effectively and there should be provision of enough storage space for expansion to facilitate proper documents management at Unique SACCO.